IFC Model Restructuring Framework for Efficient Bulk-loading to Object-relational IFC Model Server - Cho, Chi Yon; Won, Jongsung; Ham, Sungil (KSCE Journal of Civil Engineering, 2018)
This study proposes an IFC model restructuring framework for importing a large IFC model into an Object-Relation-database-based Industry Foundation Classes (OR-IFC) server. The purpose of using an IFC server is to facilitate collaboration by exchanging Building Information Modeling (BIM) data among construction project participants. However, the large size of IFC files could require several days to upload to the server and cause a time delay in terms of information exchange. For example, with a non-optimized algorithm, it can take several days to import a 111 MB model file into the IFC server and an import failure can occur with large model files that exceeds 300 MB due to the many cycles of iterations in the search and mapping process for IFC entities and object identifiers. Therefore, the authors proposed a new restructuring algorithm and a bulk-loading method in order to import IFC data into the server in a timely manner. The idea of bulk-loading is to presort and group all the IFC instances by IFC class into blocks. As a result, the import time for a 61 MB model required 56 seconds, and a 111 MB office-building model and a 346 MB building model were imported in 2 min 37 sec and 14 min 11 sec, respectively. The experimental result have shown that the import speed was improved by 30 times faster than the previous NoSQL-based approach. Therefore, the proposed method is anticipated to enable efficient information exchange among project participants in future BIM projects.